(untitled) (UUM Journal of Legal Studies, 2015)
The ever-controversial issue of sexual minorities and homosexuality has remained contentious since the very term was introduced, primarily because it has been seen as unnatural and does not correspond with what society as well as the legal norms prevailing in the society, define as ‘normal’. It becomes imperative to briefly examine the development of the laws governing these populations and their impact on the societies’ evolving attitudes towards homosexual relationships and transgender, to show the progress of the gay liberation movement and its effects on formulation of the laws in the society. Aside from the judgment of the heterosexual world, many myths about homosexuality have been imagined. Thus, with this backdrop on the issue at hand, the authors aspire to analyze and attempt to unveil these myths, arguing about the welfare and protection of these classes of individuals who fight a daily battle to secure their identities in the society we dwell in. The authors strive to comprehend the legal status of the LGBT communities across the globe and compare their plight to that in India, to critically analyze their legal rights and interests and ensure the level of implementation in the various regimes, to comprehend the various judicial measures that have been undertaken to safeguard the very existence of such communities, and conclusively enunciate the various lessons that could be learnt from the ongoing judicial trend and how the same may be put in application considering the Indian modus operandi. The authors aim to dig deep into the concerns where these aversions in relation to homosexuality can be reversed and the society could evolve as broad-minded, understanding the concerns of such persons who live under the constant apprehension of being ‘found out’ and the various forms of discrimination and atrocities that they have faced and are still facing under the present Indian legal regime. Keywords: sexual minorities; homosexuality; legal status; judicial trends; India